Energy Yield Optimization of a Large-Scale PV Power Plant in Self-Consumption Mechanism - Şenol, Mehmet (Eastern Mediterranean University EMU, 2017)
The objective of this thesis is to optimize the design parameters of a large scale photovoltaic power plant in order to find its optimal size having the lowest payback period. A methodology is proposed to guide the investors and technical staff in the design of such a system, with core emphasis on self-consumption policy. A flowchart of the process, that uses site survey, system components, associated costs, meteorological data, load analysis, is created. A three-step algorithm is developed in order to solve the optimization problem that searches for the PV plant size having the lowest payback period. The first phase of the algorithm is to minimize the energy fed into the grid for free of charge. In other words the self-consumption is maximized. The decision variables such as the tilt angle of the PV modules, number of PV modules connected in series across a string, number of strings connected to an inverter and the number of inverters are calculated in this phase. The second phase involves maximizing the occupied land area and determining layout of the PV plant. The layout is based on consecutive PV blocks in the installation area. Number of rows and columns in a PV block are obtained in this phase. Last phase is based on the calculation of the optimal size of the PV plant, which has the lowest payback period, by using an iterative approach. Net present value analysis is used as a supplementary tool in order to allow the investor to make better judgment on the project. A case study is carried out in Cyprus International University campus in order to support the proposed methodology. The lowest payback period is achieved at 6.18 years with the total installed capacity of 712 kWp. The payback period results iv calculated by the proposed algorithm and PV*SOL Premium, which is one of the most commonly used PV planning software in the PV market, for each increment in the PV plant size are compared. The difference between the payback periods obtained from the proposed algorithm and PV*SOL Premium is 1.79% on average and 0.34% at the optimum PV plant capacity. According to the case study, a 712 kWp self-consumption PV plant can be installed on 9055 m2 of land area. The initial investment cost is calculated as € 1,063,700. The system can consume 97.92% of its own annual production while only 2.08% of the annual PV energy generation is exported to the grid. The system reaches a self-sufficiency ratio of 25.02%. The net present value is calculated as € 7,091,000. Keywords: Solar energy, large-scale PV power plant, non-incentivized self-consumption, design optimization.

ÖZ: Bu tezin amacı, büyük ölçekli fotovoltaik (FV) enerji santralinin tasarımını optimize etmektir. Öz tüketim politikasını temel alarak, böyle bir sistemin tasarımında yatırımcılara ve teknik personele rehberlik etmek için bir yöntem geliştirilmiştir. Bu bağlamda tüm süreci gösteren ve saha araştırması, sistem bileşenleri ile ilgili maliyetler, meteorolojik veriler, yük analizi konularını kapsayan bir akış şeması oluşturulmuştur. En düşük geri ödeme süresi olan FV santralini bulmak için üç adımdan oluşan bir optimizasyon algoritması geliştirilmiştir. Algoritmanın ilk aşaması, şebekeye ücretsiz olarak verilen ancak ekonomik karşılığı olamayan enerjiyi en aza indirgemektir. Bir başka değişle öz tüketimi en üst seviyeye çekmektir. FV modüllerinin eğim açısı, bir dizi boyunca seri bağlanmış FV modül sayısı, bir eviriciye bağlı dizi sayısı ve evirici sayısı gibi karar değişkenleri bu aşamada hesaplanır. İkinci aşamada, kullanılan arazinin hesaplanıp, FV santralinin yerleşimi belirlenir. Bu aşamada bir FV bloğunda bulunan yatayda ve dikeyde yerleştirilen modül sayıları belirlenir. Son aşamada ise tekrarlanan bir yaklaşım kullanılarak, en düşük geri ödeme süresi olan FV santralinin optimum büyüklüğünü hesaplanır. Net bugünkü değer analizi, yatırımcının projeyle ilgili daha iyi karar vermesine olanak tanıyacak şekilde geri ödeme süresi analizi ile birlikte kullanılır. Önerilen metodolojiyi desteklemek için bir üniversite kampüsü için durum çalışması yapılmıştır. En düşük geri ödeme süresini olan 6.10 seneyi veren FV santralinin optimum kapasitesi 712 kWp olarak hesaplanmıştır. FV santralinin büyüklüğündeki her artış için önerilen algoritma ile hesaplanan geri ödeme süresi sonuçları PV*SOL Premium yazılımından elde edilen sonuçlar ile karşılaştırılmıştır. Önerilen vi algoritmanın sonuçları ile PV*SOL Premium yazılımından elde edilen sonuçlar arasında yalnızca %3’lük bir fark olduğu görülmüştür. Yapılan durum çalışmasına göre, 9055 m2 arazi üzerine öz tüketim prensibi ile çalışan 712 kWp gücünde bir FV tesisi kurulabilmektedir. Sistemin ilk yatırım maliyeti 1.06.700 € olarak hesaplanmıştır. Sistem, kendi yıllık üretiminin %97,92'sini tüketebilirken, yıllık PV enerjisinin yalnızca %2,08'ini elektrik şebekesine verilmektedir. Sistem, %25,02'lik kendi kendine yeterlilik oranına ulaşmaktadır. Net bugünkü değer 7.091.000 € olarak hesaplanmıştır. Anahtar Kelimeler: Güneş enerjisi, büyük ölçekli FV santrali, teşviksiz öz tüketim, tasarım optimizasyonu.
Doctor of Philosophy in Electrical and Electronic Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2017. Supervisor: Prof. Dr. Osman Kükrer.
Keywords: Electrical and Electronic Engineering; Photovoltaic power systems; Photovoltaic power generation; Use of-Solar Energy; Solar energy; large-scale PV power plant; non-incentivized self-consumption; design optimization